Unraveling the Effects of Melissa officinalis L. on Cognition and Sleep Quality: A Narrative Review - Oliveira, Maria Vitória Barroso; Garguerra, Júlia Aparecida; Lamas, Caroline Barbalho; Laurindo, Lucas Fornari; Rodrigues, Victória Dogani; Sloan, Kátia Portero; Sloan, Lance Alan; Chagas, Eduardo Federighi Baisi; Guiguer, Elen Landgraf; Detregiachi, Claudia Rucco Penteado; Miglino, Maria Angélica; de Souza Bastos Mazuqueli Pereira, Eliana; et al. (MDPI, 2025)
The aging process is closely linked to cognitive decline, and numerous studies have demonstrated a decrease in both the quality and quantity of sleep in the general population. Melissa officinalis (lemon balm) is a plant rich in bioactive compounds, including flavonoids, phenolic acids, and essential oils, which are responsible for its neuroprotective and antidepressant properties. Its positive effects on the sleep quality are probably, at least in part, attributable to the presence of rosmarinic acid, which modulates γ-aminobutyric acid transaminase activity. This review aimed to investigate the effects of M. officinalis on cognition and sleep quality in human clinical trials. For cognition, studies have shown that the plant improved cognitive performance and mood. In elderly individuals with mild cognitive impairment or early Alzheimer's disease, extracts standardized in rosmarinic acid stabilized cognitive functions and reduced neuropsychiatric symptoms such as agitation. Regarding sleep, a combination of lemon balm and valerian significantly improved sleep quality in postmenopausal women. Isolated lemon balm extracts also reduced sleep disorders in cardiac patients. When compared to citalopram, lemon balm enhanced the quality of life, including sleep quality. It is concluded that lemon balm has the potential to improve cognition and sleep quality; however, robust evidence is needed, as more rigorous trials are required.